Search for Sneutrino Production in e mu Final States in 5.3 fb(-1) of p(p)over-bar Collisions at root s = 1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ratoff, P. N.; et al. (Amer Physical Soc, 2010)
We report the results of a search for R parity violating (RPV) interactions leading to the production of supersymmetric sneutrinos decaying into e mu final states using 5.3 fb(-1) of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider. Having observed no evidence for production of e mu resonances, we set direct bounds on the RPV couplings lambda'(311) and lambda(312) as a function of sneutrino mass.